2016
DOI: 10.1128/msphere.00051-16
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Gene Expression Is Responsive to Starvation Stress and Developmental Transition in Trypanosoma cruzi

Abstract: Chagas disease is caused by insect-transmitted Trypanosoma cruzi. Halting T. cruzi’s life cycle in one of its various human and insect life stages would effectively stop the parasite’s infection cycle. T. cruzi is exposed to a variety of environmental conditions in its different life stages, and gene expression must be remodeled to survive these changes. In this work, we look at the impact that one of these changes, nutrient depletion, has on the expression of the 20 gene products encoded in the mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(72 citation statements)
references
References 68 publications
(74 reference statements)
8
62
0
1
Order By: Relevance
“…Our previous 109 work is the impetuous for these experiments, in which we showed that culture-derived 110 trypomastigotes exhibit higher levels of many mitochondrial RNAs relative to log-stage 111 epimastigotes. However, mRNA abundance is actually highest in the starved epimastigotes 112 rather than in the trypomastigotes of a mixed culture (Shaw et al, 2016). Therefore, we 113 wondered how transient the changes in gene expression upon starvation actually were.…”
Section: Results 105mentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous 109 work is the impetuous for these experiments, in which we showed that culture-derived 110 trypomastigotes exhibit higher levels of many mitochondrial RNAs relative to log-stage 111 epimastigotes. However, mRNA abundance is actually highest in the starved epimastigotes 112 rather than in the trypomastigotes of a mixed culture (Shaw et al, 2016). Therefore, we 113 wondered how transient the changes in gene expression upon starvation actually were.…”
Section: Results 105mentioning
confidence: 98%
“…Theoretically these conditions 229 could reduce rather than increase the need for these RNAs. This is particularly true as most 230 mitochondrial mRNAs encode ETC subunits, and two nuclear-encoded ETC subunits were not 231 found to increase in abundance during starvation ( (Shaw et al, 2016); antibodies cannot be 232 generated to subunits encoded in the mitochondrial genome). To explore this further we asked 233 whether the rRNAs that were increased in starved epimastigotes were incorporated into 234 ribosomes or instead accumulated as non-associated RNAs.…”
Section: Results 105mentioning
confidence: 99%
See 1 more Smart Citation
“…The infectious stage of T. cruzi (trypomastigote) was obtained by in vitro differentiation of epimastigotes in RPMI medium [5], followed by infection to the host 3T3-Swiss Albino fibroblast cells. The parasitehost co-culture was maintained in DMEM supplemented with 10 FBS at 37C under 5 CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…the metacyclogenesis have been described such as morphology, infectivity and gene expression [10][11][12], the differences in the energetic metabolism throughout the culture growth have not yet been explored. Shah-Simpson et al [13] described the glucose metabolism in epimastigotes, metacyclic trypomastigotes and amastigotes determining the differences in excretion of pyruvate, acetate and alanine.…”
Section: Discussionmentioning
confidence: 99%